2014
DOI: 10.1371/journal.pone.0086858
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness and Harm-Benefit Analyses of Risk-Based Screening Strategies for Breast Cancer

Abstract: The one-size-fits-all paradigm in organized screening of breast cancer is shifting towards a personalized approach. The present study has two objectives: 1) To perform an economic evaluation and to assess the harm-benefit ratios of screening strategies that vary in their intensity and interval ages based on breast cancer risk; and 2) To estimate the gain in terms of cost and harm reductions using risk-based screening with respect to the usual practice. We used a probabilistic model and input data from Spanish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
160
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(174 citation statements)
references
References 46 publications
6
160
2
1
Order By: Relevance
“…The concept of big data makes possible the integration of current, previous, and future breast examination data with a multitude of other data sources, such as electronic health records, genomic analysis, and lifestyle tracking. This integration can make future breakthroughs in risk modeling and disease detection possible [36]. To realize these breakthroughs, breast imagers and data engineers will need to collaborate.…”
Section: Data To Big Data and Data Miningmentioning
confidence: 99%
“…The concept of big data makes possible the integration of current, previous, and future breast examination data with a multitude of other data sources, such as electronic health records, genomic analysis, and lifestyle tracking. This integration can make future breakthroughs in risk modeling and disease detection possible [36]. To realize these breakthroughs, breast imagers and data engineers will need to collaborate.…”
Section: Data To Big Data and Data Miningmentioning
confidence: 99%
“…Family history of breast cancer and increased breast density are known to increase the risk of breast cancer [30][31][32], and some authors have suggested using these parameters to determine who should be screened [23,29]. In particular, first-degree family history has been emphasized as a criterion for risk-based screening [27], and prior studies evaluating risk depending on degree of family history of breast cancer have used a stratification strategy similar to ours [28].…”
Section: Price Et Almentioning
confidence: 99%
“…Because of its emphasis on patient context, this qualification reignited interest in a risk-based approach to screening mammography in women younger than 50 years old [10,[23][24][25][26][27][28]. Specifically, it has been suggested that routine screening mammography be used for 40-to 49-year-old women only when there is a family history of breast cancer or dense breasts (or both) [23,29], because these factors are known to increase the risk of breast cancer [30][31][32]. …”
mentioning
confidence: 99%
“…Las estimaciones son tan variables como los méto-dos para estimarlo 22 . A pesar de las intensas estrategias de cribado, la mortalidad asociada a cáncer de mama no letal ha disminuido el 8%, mientras que la mortalidad por cáncer de mama en general se ha reducido en un 28%.…”
Section: Sobrediagnóstico En El Cáncer De Mamaunclassified